Food matrix and processing influence on carotenoid bioaccessibility and lipophilic antioxidant activity of fruit juice-based beverages. Issue 1 (26th October 2015) - Rodríguez-Roque, María Janeth; de Ancos, Begoña; Sánchez-Vega, Rogelio; Sánchez-Moreno, Concepción; Cano, M. Pilar; Elez-Martínez, Pedro; Martín-Belloso, Olga
Abstract : Food matrix and food processing are factors of importance in designing food and beverages with a high content of bioaccessible carotenoids. Abstract : The biological activity of carotenoids depends on their bioaccessibility and solubilization in the gastrointestinal tract. These compounds are poorly dispersed in the aqueous media of the digestive tract due to their lipophilic nature. Thus, it is important to analyze the extent to which some factors, such as the food matrix and food processing, may improve their bioaccessibility. Beverages formulated with a blend of fruit juices and water (WB), milk (MB) or soymilk (SB) were treated by high-intensity pulsed electric fields (HIPEF) (35 kV cm −1 with 4 μs bipolar pulses at 200 Hz for 1800 μs), high-pressure processing (HPP) (400 MPa at 40 °C for 5 min) or thermal treatment (TT) (90 °C for 1 min) in order to evaluate the influence of food matrix and processing on the bioaccessibility of carotenoids and on the lipophilic antioxidant activity (LAA). The bioaccessibility of these compounds diminished after applying any treatment (HIPEF, HPP and TT), with the exception of cis -violaxanthin + neoxanthin, which increased by 79% in HIPEF and HPP beverages. The lowest carotenoid bioaccessibility was always obtained in TT beverages (losses up to 63%). MB was the best food matrix for improving the bioaccessibility of carotenoids, as well as the LAA. The results demonstrate that treatment and food matrix modulated the bioaccessibility of carotenoids as well as the lipophilic antioxidant potential of beverages. Additionally, HIPEF and HPP could be considered as promising technologies to obtain highly nutritional and functional beverages.